Lectins for the detection of IgM antibodies to T. gondii in the diagnosis of acute toxoplasmosis by immunofluorescence test - I. T. I. Nojimoto; S. Hoshino-Shimizu; T. K. Nagasse-Sugahara; M. E. Camargo (Revista do Instituto de Medicina Tropical de São Paulo, 1987)
Lectins were labeled with fluorescein and tried as conjugates in the immunofluorescence (IP) test for the detection of IgM antibodies to T. gondii, in the diagnosis of acute toxoplasmosis. This approach was an attempt to find alternative reagents for anti-human IgM fluorescent conjugates (AHIgMFC), which contain quite frequently anaibcdies to toxoplasma, as contaminants, due to natural T. gondii infections among animals used for imunization. Lentil (Lens culinaris) lectin fluorescence conjugates (LcFC) provided most satisfactory results. The evaluation of LcFC carried out in a total of 179 sera from patients with acute and chronic toxoplasmosis, with non-related infections or healthy subjects, gave high values of relative efficiency, co-positivity and co-negativity indices, respectively 0.989, 0.969 and 1.000, in reference to the conventional AHIgMFC. Moreover, three batches of LcFC successively prepared gave reproducible test results. The advantage of LcFC as an alternative reagent for the serodiagnosis of acute toxoplasmosis is supported by practical aspects of its preparation.